UJARAN KEBENCIAN NETIZEN INDONESIA DI AKUN TWITTER ES THE: TINJAUAN LINGUISTIK FORENSIK - Syafruddin; Aziz Thaba; Refisa Ananda (STKIP Siliwangi, 2024)
This study aims to describe the form of netizens' hate speech on the @esteh_indonesia Twitter account which can be categorized as a violation of the law. This research is included in the qualitative research used to describe netizens' hate speech in @esteh_indonesia Twitter comments using forensic linguistic reviews. The methods and techniques used are the listening method and the note-taking technique. Listening is done by observing the hate speech of netizens on the Twitter account @esteh_indonesia. After that, the data that has been selected purposively is copied and then analyzed by collecting data that has been recorded in one folder, classifying and analyzing the data based on the form of hate speech with the guidelines of the Police circular regarding hate speech on social media. The results of the study prove that there are five forms of netizens' hate speech in the Twitter comments of the @esteh.indonesia account: 1) insults, 2) defamation, 3) blasphemy, 4) provoking, and 5) hoax. The results of this study can increase public awareness about the existence of hate speech on social media platforms, especially Twitter. This can encourage people to be more careful in interacting online.